Systematic identification and analysis of WRKY transcription factors reveals the role of MrWRKY14 in Myrica rubra - Fan, Xiurun; Chen, Minghui; Zhang, Huiling; Liu, Yumeng; Yang, Meng; Ye, Chengyang; Gu, Hailing; Xu, Kai; Wu, Boping (Frontiers in Plant Science, 2025)
Bayberry (Myrica rubra) is a significant subtropical fruit tree, renowned for its distinctive flavor and high nutritional value. WRKY transcription factors are a class of plant-specific zinc-finger proteins that play critical roles in plant growth and development, secondary metabolism, and responses to abiotic stress. However, there is currently limited information about the WRKY gene family in bayberry. This study conducted a systematic bioinformatics analysis of 55 WRKY genes in bayberry, elucidating their phylogenetic relationships, gene structures, conserved motifs, and syntenic characteristics. The results demonstrated that these WRKY family members could be classified into five subfamilies, with each gene containing at least one WRKY domain. The bayberry WRKY genes exhibited significant variations in gene length and intron-exon numbers, while maintaining relatively conserved gene structures within each subfamily. The promoters of WRKY gene members contained multiple regulatory elements, including hormone-responsive elements, light-responsive elements, and abiotic stress-responsive elements. Collinearity analysis revealed that the WRKY family in bayberry experienced six segmental duplication events. Inter-species synteny analysis demonstrated high collinearity between bayberry and Actinidia spp., indicating evolutionary conservation of WRKY genes across different plant species. It was observed that bayberry WRKY genes exhibited significant differential expression across different cultivars and developmental stages of fruits through expression pattern analysis. Further research indicated that MrWRKY14, a member of the bayberry WRKY family, significantly enhanced the promoter activity of MrSWEET1, thereby influencing the process of sugar accumulation. These findings not only provide an important reference for the genome-wide identification of WRKY gene families in plants but also lay a solid foundation for future in-depth functional analysis of bayberry WRKY genes.